VARIASI JUMLAH TUMBUKAN PADA CAMPURAN BETON ASPALTERHADAP NILAI DENSITY DAN VOID IN THE MIX ( VITM ) - Syaiful Amal, Andi (Jurnal Gamma, 2010)
TAsphalt concrete mix is one type of flexible pavement layer. Asphalt concrete mixture consistsessentially of coarse aggregate, fine aggregate, filler and binder. Aggregate used may be natural orthe result of processing and can also be the artificial aggregate. While grading for asphalt concretemix is Continuously graded. This study aimed to assess the absolute density, ie density of a pavementlayer maximum value. Absolute density is needed in order to predict the quality of road pavementlayers in accordance with the variation of the number of collisions 2x75, 2x150, 2x200, 2x300 and2x400 blows. Then studied the effect of variations in the collision of the Marshall test parameters,which include density, stability, voids of mineral aggregate (VMA), voids filled with asphalt (VFWA),voids in the mix (VITM), flow and marshall qoutient. The results showed a variation of the effect ofcollisions on the value of VITM. specially for heavy traffic comparison of values obtained onvariation of the collision VITM 2x150, 2x200, 2x300 and 2x400 to VITM standard is between 50-60% (collision 2x75). These results indicate that all kinds of variations of the collision above thestandard collision will result in fatigue of materials, pavement materials become damaged as aresult. From the results of this study also obtained the optimum asphalt content for heavy traffic,moderate and mild, respectively, are 6.44%, 6.59% and 6.86%. From the results of this study alsoobtained a density value of the field whose value is based on the optimum asphalt content in successionto heavy traffic, medium and light, which is 2.35 g / cc, 2.35 g / cc and 2.36 gr/cc